Managing Learning: Mistakes Feedback Oral and Written Work - Wisran Wisran; Dewi Furwana; Andi Husni A. Zainuddin; Fauziah Tanjung (Faculty of Education and Teacher Training of UIN Palopo, 2025)
This study explores the critical role of mistakes and feedback in the learning process, focusing on the management of student performance in oral and written assessments. Mistakes are considered an inherent part of learning, so this study discusses strategies to effectively assess student performance, provide timely feedback, and create an environment that encourages continuous improvement. The first part of this study highlights that mistakes can be valuable learning opportunities. The study delves into the details of providing feedback in oral tasks, including how to deliver constructive feedback, encourage student reflection, identify areas for improvement, and motivate active participation in the learning process. The next section of the study addresses another crucial aspect of feedback, focusing on written assessments. It emphasizes effective methods to provide feedback to help students refine their writing skills. Additionally, it discusses how feedback can foster a growth mindset, increase resilience, and create a positive learning environment. The conclusion of this study advocates a holistic approach to learning, recognizing the role of mistakes while emphasizing the transformative impact of constructive feedback. By addressing both oral and written components, this study offers insights into effectively managing learning and creating an educational environment that supports continuous growth and improvement.